Method for prevention of seepage due to excavation in sand - Tey, Jack Hong (2017)
Sheet piles are commonly used for retaining walls or other geotechnical structures to prevent the movement of soil. However, sheet pile walls are not waterproof. When water seeps through a sheet pile wall, soil particles may also be washed away and causes ground subsidence. Thus, it is necessary to develop a method to construct sheet pile walls that are waterproof of having the ability to prevent soil to be washed through the sheet piles with water. In this project, some models tests were carried out to explore methods that can be used to construct waterproof sheet pile walls. Two different treatment methods for the sheet pile walls were studied, namely, treatment at the joint of the sheet piles (Method 1) and treatment for the soil behind the joint (Method 2). A range of sealants including hydrogel, bentonite and mixture of hydrogel-bentonite (H-B), kaolin and mixture of hydrogel-kaolin (H-K) were investigated using these two methods. The effectiveness of water cut-off property and expansion rate of each sealant were studied using permeability test and expansion test respectively. This project reveals that hydrogel can expand and seal the sheet pile joint after it contacts with water. It reduces the seepage through the sheet pile wall completely while having a huge expansion rate for both methods proposed. Therefore, the sheet pile joints need to be treated with care to avoid over usage and ensure the vertical alignment of the sealant. Kaolin is not recommended as water sealant for sheet pile walls in Method 1 because it is easy to be flushed out from the sheet pile joint. However, the seepage through the sheet piles model was reduced completely by using bentonite, H-B mixture (3% of hydrogel or above) and H-K mixture (4% of hydrogel or above) in Method 1. In addition, the expansion rate of these sealants is favourable as the sealants could expand and seal the sheet pile joint. In Method 2, H-B mixture (4% of hydrogel in this project) can reach an 80% reduction in seepage effect of the model. On the other hand, for kaolin and H-K mixture, the sheet pile joints also need to be treated with care to ensure the vertical alignment to achieve a lower seepage effect in Method 2.